"Exploitation Creep" and Development: A Response to Janie Chuang. (2014) - Ahmed, Aziza
Abstract : In her article Exploitation Creep and the Unmaking of Human Trafficking Law, Janie Chuang insightfully describes transformations in the discourse on trafficking as it shifted from sex trafficking to human trafficking, and as human trafficking came to be understood as forced labor, and now modern day slavery. With each of these transformations, the United States government, self-anointed "global sheriff" of anti-trafficking efforts, deepened its emphasis on a prosecution-oriented strategy focused on individual perpetrator accountability. As an alternative trajectory, Chuang identifies and convincingly argues for a labor-rights approach that takes into consideration the structural causes of exploitation in the labor market, including poverty, unemployment, discrimination, and conflict.